Giant Oocyte with Two Polar Bodies: Case Report of Self Patient - Jayaram , C.; Sultana, Nyma; Amin, Jayesh; Makwana, Paresh; Kousar, Mohammad Sehba; Patel, Bharvi (International Journal of Scientific Research in Biological Sciences, 2022)
Here we report a case of the giant oocyte with two polar bodies, with the immense of ART technology, formally giant oocytes are a very rare phenomenon among humans and embryos may develop from oocytes. (1,2), and Giant oocytes are defined to have a 35% larger diameter and twice the volume of the normal oocyte. Fertilization and progression of a giant oocyte are suspected to be the cause of triploidy, which is defined as triploidy with two maternal and one paternal complement. The hypothesis for the mechanism of their formation is a cytoplasmic fusion of two oogonia and the second one is the lack of cytokinesis during mitotic divisions in an oogonium. In this case report, we present one Giant oocyte with two distinct polar bodies. Giant oocytes can develop into embryos that are morphologically normal, but genetically abnormal, embryologist should aware of this phenomenon. For this reason, the scientific aim of this report is to present make awareness among practicing embryologists.